2020
DOI: 10.1590/1980-549720200105
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças nas condições socioeconômicas e de saúde dos brasileiros durante a pandemia de COVID-19

Abstract: RESUMO: Objetivo: Descrever as mudanças nas condições socioeconômicas e de saúde dos brasileiros durante a pandemia de COVID-19. Métodos: Estudo transversal com dados de pesquisa de comportamentos realizada pela internet de 24 de abril a 24 de maio de 2020 com 45.161 participantes recrutados por amostragem em cadeia. Foi feita uma análise descritiva de temas abordados na pesquisa: adesão às medidas de restrição social, diagnóstico do novo coronavírus, situação de trabalho e rendimentos, dificuldades nas at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
48

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 33 publications
3
17
0
48
Order By: Relevance
“…As for the intermediation of behavioral indicators, the intake of healthy food and practice of physical activity during the pandemic showed a positive influence on emotional well-being, while excessive screen time negatively affected the outcome. In turn, associations with the distal variables corroborate previous results [5], with less affluent adolescents being the most affected and females reporting problems more often than males.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As for the intermediation of behavioral indicators, the intake of healthy food and practice of physical activity during the pandemic showed a positive influence on emotional well-being, while excessive screen time negatively affected the outcome. In turn, associations with the distal variables corroborate previous results [5], with less affluent adolescents being the most affected and females reporting problems more often than males.…”
Section: Discussionsupporting
confidence: 87%
“…4 Missed going to school during home confinement. 5 Lack of concentration was one of the difficulties in following non-face-to-face classes. 6 Often felt lonely during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any impediment or possibility of thwarting these basic human objectives, or any danger to the defenses that protect them or the conditions on which they are set are considered psychological threats [14]. COVID-19 threatens all layers of Maslow's hierarchy, and deficits in each of these basic needs have deleterious consequences for our mental health [15]. 25.8% of the individuals could not work, and the group of informal workers was the most affected (50.6%).…”
Section: Discussionmentioning
confidence: 99%
“…The latter displayed a great impact on the life of the population in several aspects, mainly on mental health. Since the vast majority of the Brazilian population adhered to self-isolation, leaving home only for essential activities, a study carried out in Brazil, with individuals from different states, showed that more than half of the participants had anxious feelings after the arrival of the pandemic, 40.2% felt depressed and 44.9% started having problems with sleep (Almeida et al, 2020). Such circumstances can also be seen in other studies; a survey published by Ciencia & Saúde Coletiva magazine in June 2020, confirms that the vast majority of Brazilians had increased levels of depressive symptoms, anxiety and changes in hours of sleep after the outbreak of COVID-19.…”
Section: Introductionmentioning
confidence: 99%